2004
DOI: 10.1207/s15328015tlm1603_11
|View full text |Cite
|
Sign up to set email alerts
|

A Resident Research Director Can Improve Internal Medicine Resident Research Productivity

Abstract: Our analysis suggests that an RRD can enhance resident scholarly productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Similar investigations have been conducted in other specialties: family medicine [2], preventive medicine [3], internal medicine [4], and urology [5,6]. Kruse et al [2] determined that the presence of full-time research faculty members is the most important factor for productivity among both large and small family residency programs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar investigations have been conducted in other specialties: family medicine [2], preventive medicine [3], internal medicine [4], and urology [5,6]. Kruse et al [2] determined that the presence of full-time research faculty members is the most important factor for productivity among both large and small family residency programs.…”
Section: Discussionmentioning
confidence: 81%
“…Salive and Stein [3] illustrated that self-motivation and academic appointment were among the strongest predictors of research productivity for graduates of preventive medicine residencies. With respect to internal medicine residents, Durning et al [4] demonstrated that a designated research director increases research productivity. For urology residents, Hellenthal et al [5] showed that protected research time and previous publications before residency were the greatest predictors of research productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The program described, however, is community based and the interventions and outcomes described are similar to those previously used and found in other IM residency programs. 3,[5][6][7]9,10 Second, it is unknown whether residents would have completed the observed amount of research independent of the interventions. Although it is theoretically possible that residents in the program during the latter part of the study period were inherently more inclined toward research than their earlier counterparts, we feel this is unlikely given the significant increase in research activity seen over a short time.…”
Section: Discussionmentioning
confidence: 99%
“…29,37 With exposure to rotation directors, who have extensive research experience, the residents benefit from their expertise and the rotation becomes an academic research block. The CDB directors select faculty who are outstanding teachers to lead each interactive seminar.…”
Section: Tion a Cdb Preparatory Workhop Formentioning
confidence: 99%
“…4,5 The importance of a dedicated research rotation and the presence of a research director have been highlighted as strategies to enhance resident research. 28,29 To address the challenges of promoting academic scholarship and enhancing research productivity of our housestaff, in July 2002 we instituted a new curriculum within our pediatric training program. One of its key elements was the introduction of a 3-month required block rotation, the careerdevelopment block (CDB), in the PGY-3 year.…”
mentioning
confidence: 99%